1999
DOI: 10.1177/105345129903400406
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing the Rough Edges of Classroom Transitions

Abstract: Many students with learning and attentionrelated disabilities have difficulty dealing with classroom transitions. In this article, the problems that are often associated with this classroom activity are discussed within the context of effective teaching. Short case studies are provided to show how behavior problems escalate when effective teaching methods are not utilized. Several transition techniques are suggested. or many young students, transitions between activities and lessons are problematic. Students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
9
0
3
Order By: Relevance
“…Classroom rules are stimuli that establish collective behavioral expectations that define and shape behaviors and provide order, discipline, and control over students to protect people and allow learning to occur unimpeded. Educators and researchers have recommended that teachers set behavioral expectations by developing one set of brief (three to five) classroom rules (Buck, 1999; Heins, 1996; Malone & Tietjens, 2000). Different classroom activities have different behavioral expectations, however.…”
mentioning
confidence: 99%
“…Classroom rules are stimuli that establish collective behavioral expectations that define and shape behaviors and provide order, discipline, and control over students to protect people and allow learning to occur unimpeded. Educators and researchers have recommended that teachers set behavioral expectations by developing one set of brief (three to five) classroom rules (Buck, 1999; Heins, 1996; Malone & Tietjens, 2000). Different classroom activities have different behavioral expectations, however.…”
mentioning
confidence: 99%
“…Consistent with the current findings, teachers in previous studies have also cited behavior management [ 26 , 60 , 63 ] and developmental appropriateness concerns [ 60 ] as barriers to use of MI. It is not surprising that teachers perceived that MI products may lead to disruptions and behavior management challenges as research has shown that student misbehavior occurs primarily when students are out of their seats in the classroom [ 64 , 65 ]. Further, teachers who have limited experience and training in managing active environments may perceive times that children are out of their seats in the classroom as out of control.…”
Section: Discussionmentioning
confidence: 99%
“…He also recorded up to 30 different transitions during a typical elementary school day and identified three sequential transition phases: "(1) an abandonment of a previous activity with its relevant milieu; (2) a movement toward the second activity; (3) 'getting into' the second activity with its milieu" (Gump, 1987, p. 722). This art of shifting student focus is worthy of study as evidenced by its inclusion in a variety of classroom management texts and articles directed at preservice and inservice teachers (Buck, 1999;Burden, 2006;Cangelosi, 2008;Charney, 2002;Hemmeter, Ostrosky, Artman, & Kinder, 2008;Jones & Jones, 2010;McIntosh, Herman, & Sandford, 2004;Nix, 2008;Smythe, 2002;Weinstein, 2007;Wood, 1999).…”
Section: Classroom Management and Transitionmentioning
confidence: 98%